تجلّيات السّخرية في شعر النّقائض –ردّ جرير على خُصومه أنموذجا- - حيمور, سهى; بومهرة, عبد العزيز (جامعة الوادي - University of Eloued, 2023)
ينصرف القصد في هذا البحث إلى دراسة وتحليل نماذج من شعر النّقائض لاستخراج أهم تجليات السّخرية فيه، هذا النّوع من الخطاب السّاخر يعود سلبا على الفرد أولا، ثمّ المجتمع بأكمله؛ إذ يؤثر على نفسيات الأفراد وتصرّفاتهم، ومنبع هذا الخطاب هو النرجسيّة وحب الظهور والتعالي؛ الّتي يُعزَى سبب تولّدها إلى شخصيّة الشّاعر وعلاقاته مع خصومه والبيئة المحيطة به؛ وذلك بتصويره مخالفا أو خصما، ولبيان ذلك أخذنا شعر النّقائض الذي ظهر في العصر الأموي نموذجا للدّراسة، فالنّقائض في الأصل مُنافرات وخُصومات شعرية تٌبنى على السّخرية، وليست عداوة، بالمعنى الحقيقي؛ إذ إنّها أقرب إلى المباريات في ادعاء معرفة الآخر وإلصاق الخصال الذّميمة به، وخصصنا البحث في سخرية جرير بخصومه، متوخين في ذلك المنهج الوصفي التحليلي. The main aim of the present study is to examine and analyze some samples of antitheses satirical poetry by highlighting some of their most essential demonstrations of irony. Regarding this typical discourse of satire, it is worth saying that it has a drastic negative effect on the individual in the first place as well as society as a whole since it impacts negatively man’s psyche and their attitudes. Moreover, it can be said that several factors are placed at the origin of such a discourse including narcissism and one’s feeling of superiority which are considered as some of defining attributes of the poet’s personality in his attempt to expose human flaws in society. Following a descriptive analytical approach, a case study has been selected so that to meet the study objectives in which one opted to examine some examples of antitheses in poetry that appeared during the Umayyad period. In fact, satire as a poetic device is characterized by contradictions that are ironical in essence. To better elucidate this reality, one seeks to shed light on Jarir’s ironical renditions.
Keywords: السّخرية، النّقائض، التجلّيات، جرير، الفرزدق، الأخطل ;; Satire, Antitheses, Demonstrations, Djarir, Farazdaq, Akhtal